Selective phosphodiesterase-5 (PDE-5) inhibitor vardenafil ameliorates renal damage in type 1 diabetic rats by restoring cyclic 3′,5′ guanosine monophosphate (cGMP) level in podocytes - Fang, Lilla; Radovits, Tamás; Szabó, Gábor; Mózes, Miklós M.; Rosivall, László; Kökény, Gábor (Nephrology, dialysis, transplantation, 2013)
Diabetic nephropathy (DN) is characterized by podocyte damage and increased phosphodiesterase-5 (PDE-5) activity-exacerbating nitric oxide (NO)-cyclic 3′,5′ guanosine monophosphate (cGMP) pathway dysfunction. It has been shown that PDE-5 inhibition ameliorates DN. The role of podocytes in this mechanism remains unclear. We investigated how selective PDE-5 inhibition influences podocyte damage in streptozotocin (STZ) diabetic rats.Male Sprague-Dawley rats (250-300 g) were injected with STZ and divided into two groups: (i) STZ control (non-treated, STZ, n = 6) and (ii) STZ + vardenafil treatment (10 mg/kg/day, STZ-Vard, n = 8). Non-diabetic rats served as negative controls (Control, n = 7). Following 8 weeks of treatment, immunohistochemical and molecular analysis of the kidneys were performed.Diabetic rats had proteinuria, increased renal transforming growth factor (TGF)-β1 expression and podocyte damage when compared with controls. Vardenafil treatment resulted in preserved podocyte cGMP levels, less proteinuria, reduced renal TGF-β1 expression, desmin immunostaining in podocytes and restored both nephrin and podocin mRNA expression. Diabetes led to increased glomerular nitrotyrosine formation and renal neuronal nitric oxide synthase and endothelial nitric oxide synthase mRNA expression, but vardenafil did not influence these parameters.Our data suggest that a dysfunctional NO-cGMP pathway exacerbates podocyte damage in diabetes. In conclusion, vardenafil treatment preserves podocyte function and reduces glomerular damage, which indicates therapeutic potential in patients with DN.